ANALISA PERSEPSI MAHASISWA TERHADAP HASIL AUDIT DAN LAPORAN KEUANGAN AUDITAN DALAM KAITANNYA DENGAN TANGGUNG JAWAB, KEANDALAN DAN KEGUNAAN UNTUK MENILAI KINERJA PERUSAHAAN MASA DEPAN - Gamaliel, Hendrik (Jurnal Organisasi dan Manajemen, 2007)
One of factors causing expectation gap is difference in perception of expectation on audited financial statements among users of audited financial statements. The different perception rises due to different perspective in dimensions of responsibility, reliability, and usefulness of audited financial statements. Expectation gap is a rising problem that can influence credibility of accountant profession. The aim of this research is to analyze perception of student empirically - particularly accounting and management students- on audit result and audited financial statements in relation to responsibility, reliability and usefulness of audited financial statements. This research used students as proxy of financial statement users.Data was collected through questionnaire using random sampling method. Sample was student of Accounting and Management Departments attending Profession Education and S2 program in Faculty of Economics and Business, Gadjah Mada University Yogyakarta (UGM). It used research instrument of Best, Buckby, & Tan (2001), with few necessary modifications. Testing used one way analysis of variance (ANOVA). Result of the research indicated empirical evidence that there was different perception among student, particularly accounting and management student, on audit result and audited financial statements in relation to dimension of auditor responsibility. Meanwhile, in relation to dimensions of reliability, and usefulness of audit result and audited financial statements, there was no different perception.